2018
DOI: 10.1016/j.isci.2018.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Negative Regulation of BOK Expression by Recruitment of TRIM28 to Regulatory Elements in Its 3′ Untranslated Region

Abstract: SummaryBCL-2-related ovarian killer (BOK) is a pro-apoptotic BAX-like member of the BCL-2 family with suggested tumor suppressor activity. The molecular mechanisms regulating BOK expression are poorly understood and fail to explain a frequent lack of concordance between protein and transcript levels. Here, we describe a potent post-transcriptional mechanism that negatively regulates BOK expression mediated by conserved (AU/U)-rich elements within its 3’ UTR. Using proteomics approaches we identified TRIM28 as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…TRIM28 gene is highly expressed in different cancer types, and higher expression frequently correlates with poor patient prognosis [ 14 , 15 , 37 , 38 , 39 ]. Recently, Fernandez-Marrero Y. et al [ 40 ] have reported a significant association of TRIM28 expression with the survival of melanoma patients. Using three independent datasets (SKCM TCGA, GSE65904, and GSE19234), we also demonstrated that TRIM28 upregulation is associated with a dramatically lower survival rate of melanoma patients.…”
Section: Discussionmentioning
confidence: 99%
“…TRIM28 gene is highly expressed in different cancer types, and higher expression frequently correlates with poor patient prognosis [ 14 , 15 , 37 , 38 , 39 ]. Recently, Fernandez-Marrero Y. et al [ 40 ] have reported a significant association of TRIM28 expression with the survival of melanoma patients. Using three independent datasets (SKCM TCGA, GSE65904, and GSE19234), we also demonstrated that TRIM28 upregulation is associated with a dramatically lower survival rate of melanoma patients.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, BOK and MCL-1 have been proposed to interact at least functionally and constitute a regulatory feedback 52 . Non-proteasomal regulation of BOK expression by mRNA stability, as proposed by Oyneagucha et al 52 , was also published by Fernandez-Marrero et al 53 . Thus, there is increasing evidence that there are levels of regulation for the expression of BOK other than proteasomal degradation.…”
Section: Discussionmentioning
confidence: 76%
“…Of note, TRIM28 and BOK levels were found to be negatively correlated in selected cancers such as hepatocellular carcinoma and kidney cancer. In those cancers, high BOK and low TRIM28 mRNA levels correlated with increased survival, and low BOK and high TRIM28 levels with decreased survival (Fernandez-Marrero et al, 2018). Translational silencing of BOK mRNA by miRNA miR-296-5p was reported by Onyeagucha et al (2017) in human breast cancer cell lines.…”
Section: Role Of Bok In Pathophysiology and Cancermentioning
confidence: 82%
“…At the level of mRNA stability and translation, BOK was found to be downregulated by binding of the miRNA miR-296-5p to its 3' UTR in breast cancer cells (Onyeagucha et al, 2017). Furthermore, destabilizing (AU/U)-rich elements [one AU-rich element (ARE) site in mouse Bok, two U-rich element (URE) sites in human BOK] were recently described in the 3' UTR of BOK (Fernandez-Marrero et al, 2018). In that study, the authors identified tripartite motif containing 28 (TRIM28), a large pleiotropic protein that is known for its many roles at the genomic level in the nucleus (Czerwinska et al, 2017), as a novel URE-binding protein triggering the degradation of human BOK mRNA (Figure 3; Fernandez-Marrero et al, 2018).…”
Section: Regulation Of Bok Expressionmentioning
confidence: 99%
See 1 more Smart Citation